2020
DOI: 10.1002/cbic.202000317
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Evolution of Fungal Cysteine Dioxygenases

Abstract: Cupin-type cysteine dioxygenases (CDOs) are non-heme iron enzymes that occur in animals, plants, bacteria and in filamentous fungi. In this report, we show that agaricomycetes contain an entirely unrelated type of CDO that emerged by convergent evolution from enzymes involved in the biosynthesis of ergothioneine. The activity of this CDO type is dependent on the ergothioneine precursor N-α-trimethylhistidine. The metabolic link between ergothioneine production and cysteine oxidation suggests that the two proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…We were intrigued about a potential connection between ergothioneine biosynthesis and thiol dioxygenation, because a number of ergothioneine biosynthetic sulfoxide synthases (EgtB homologs) catalyze cysteine dioxygenation as a significant side activity [5,17] . In certain fungi (agaricomycetes) the production of cysteine dioxide is dependent on the concomitant production of ergothioneine, adding evidence that the two compounds may participate in the same response to external signals [18] …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We were intrigued about a potential connection between ergothioneine biosynthesis and thiol dioxygenation, because a number of ergothioneine biosynthetic sulfoxide synthases (EgtB homologs) catalyze cysteine dioxygenation as a significant side activity [5,17] . In certain fungi (agaricomycetes) the production of cysteine dioxide is dependent on the concomitant production of ergothioneine, adding evidence that the two compounds may participate in the same response to external signals [18] …”
Section: Resultsmentioning
confidence: 99%
“…However, as the following analysis revealed, the primary product of ETDO is ergothioneine sulfinic acid (5) This stability allowed us to determine the origin of the two oxygen atoms of 5. We found that ETDO-catalyzed oxidation of ergothioneine in a reaction containing > 90 % heavy water (H 2 18 O) produced no detectable heavy isotopolog of 5 ([C 9 H 14 N 3 O 3 18 OS] À m/z calc. : 262.0752, Figure S15), suggesting that both oxygen atoms that are attached during oxidation derive from O 2 (Scheme 2C).…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…Other mechanisms such as mechanical destruction by fungi may also be included in keratin degradation (Korniłłowicz-Kowalska and Bohacz, 2011 ). As the disulfide bonds link polypeptides to form fibrous structures, breaking the disulfide bonds may be the first step in microbial degradation (Kasperova et al, 2013 ; Lange et al, 2016 ; Mercer and Stewart, 2018 ; Flückger et al, 2020 ). This step can be catalyzed by the produced inorganic sulfite and disulfide reductase (Korniłłowicz-Kowalska and Bohacz, 2011 ).…”
Section: Microbial Degradation Of Keratinmentioning
confidence: 99%
“…Some disulfide reductases involved in keratin degradation were shown ( Kasperova et al, 2013 ; Navone and Speight, 2018 ; Table 1 ). The roles of these enzymes in keratin degradation have been described in other literatures, which will not be described here ( Kasperova et al, 2013 ; Lange et al, 2016 ; Mercer and Stewart, 2018 ; Flückger et al, 2020 ).…”
Section: Mechanism Of Action For Keratinasementioning
confidence: 99%